PENGARUH PERSEPSI HARGA TERHADAP PERILAKU IMPULSE BUYING DENGAN KUALITAS PRODUK SEBAGAI VARIABEL MODERASI PADA KONSUMEN THE ORIGINOTE - Iriska Lampudunyo1; Iqlima Rizki Nur Annisa; Moh. Ilham (VARIABLE RESEARCH JOURNAL, 2024)
Currently, business in Indonesia has grown very rapidly, this case is the creation of various contemporary markets. The ease of the buying process, customers often make impulsive purchases or unplanned purchases. The purpose of this study is to see how price perceptions affect the impulsive buying behavior of The Originote cosmetic customers in students, especially in the Da’wah Management study program at UIN Sunan Ampel Surabaya with product quality as a moderating variable. The quantitative method was used by sending questionnaires to 35 Da’wah Management students in the 2021 batch of UIN Sunan Ampel Surabaya who use The Originote products. This study uses SPSS software as a data management tool, with research results sttating that price perception has a major influence on impulsive buying and product quality moderates the relationship between the two, with a Pearson correlation value of 0.905. In short, consumer price perceptions greatly influence impulsive buying behavior and product quality can moderate both. In short, increasing the quality of The Originote products will increase the moderating effect of price on consumer impulsive purchases